Assessing Preservice Teachers’ Challenges and Training Needs for Teaching Children with Special Educational Needs in Nigerian Regular Classes - Okonkwo , Onyekachi Ihuoma; Adedeji, Israel Olusegun Adedeji; Nwosu, Kingsley Chinaza; Mbelede, Njideka Gertrude; Anierobi, Elizabeth Ifeoma (Journal of Research in Industrial Technology and Educational Studies, 2025)
The quality of teachers is critical to the successful implementation of inclusive education. However, many teachers in Nigeria have reported low confidence in teaching children with special needs. Despite this, limited research has investigated the challenges and training needs of preservice teachers within the Nigerian context. This study explored the experiences of preservice teachers during their practicum, particularly on the challenges they encountered, and their training needs. The phenomenological qualitative approach was employed as a research design. Data were collected through focus group discussions. The sample size consisted of 40 purposively sampled preservice teachers from two colleges of education in Zamfara State. The findings from the study revealed that challenges encountered by preservice teachers in teaching students with special needs include inadequate training in inclusive practices, communication difficulties, poor infrastructure, and low inclusive self-efficacy. Participants also reported the need for practical teaching exposure, specialized communication, and better access to inclusive education resources. These point to the need to strengthen teacher education programmes for inclusive education. We recommend, among others, that the teacher training curriculum be revised to incorporate hands-on experiences for inclusive education